Aldosterone predicts major adverse cardiovascular events in patients with acute myocardial infarction. Issue 1 (25th August 2012) - Yuyun, Matthew Fomonyuy; Jutla, Sandeep K; Quinn, Paulene A; Ng, Leong L
Abstract : Objective: Aldosterone is associated with increased mortality in chronic heart failure patients and correlates with adverse outcomes after an acute myocardial infarction (AMI) in smaller cohorts. We evaluated the prognostic significance of plasma aldosterone in a large cohort of post-AMI patients in relation to major adverse cardiovascular events (MACE). Design: A prospective cohort study. Setting: University Hospitals of Leicester, UK. Patients: Consecutive 955 patients admitted with AMI. Plasma aldosterone levels were measured in these patients. Main outcome measures: During the 2 years follow-up, MACE which was a composite of all-cause mortality, myocardial reinfarction, and hospitalisation for heart failure as well as secondary endpoints (all-cause mortality and a combination of all-cause mortality and hospitalisation for heart failure), were ascertained. Results: MACE occured in N=261, 27.3%, all-cause mortality (N=114, 11.9%) and a combination of all-cause mortality and hospitalisation for heart failure (N=176, 18.4%). Patients with MACE had significantly higher median levels of aldosterone than those without (1150.1 vs 950.4 pmol/l, p=0.0118). The multivariate adjusted HR (95% CI) for log aldosterone on MACE was 1.26 (1.01 to 1.56), p=0.041; all-cause mortality 1.60 (1.13 to 2.27), p=0.008; and combination of all-cause mortality and heart failure 1.50 (1.14 to 1.97), p=0.003. Conclusions: The prognostic significance of aldosterone for a variety of endpoints in this large cohort of post-AMI patients is not new and adds to the findings by others. The magnitude of the increase in aldosterone secretion post infarction is higher than previously believed.